A Study on the Level of Intercultural Knowledge among Malaysian Secondary School Students - Marsani, Fatin Najwa Amelia; Mehar Singh, Manjet Kaur; Jaganathan, Paramaswari; Nathan Abdullah, Ahmad Sofwan; Karupiah, Premalatha (Australian International Academic Centre (AIAC), 2016)
Malaysia is typified by three major ethnic groups namely Malay, Chinese and Indian. The evolution of national unity in Malaysia, which is based on acceptance and tolerance towards different cultures has been allowed to flourish in tandem with the realization of national aspirations. Even though education system is seen to be the best tool to cultivate team work among these three major ethnic groups, contemporary research reveals that there is still a lack of intercultural embedment in both tertiary and non-tertiary settings. Worst, non-tertiary setting national schools are seen as the breeding ground of racial polarization. Thus, the main objectives of this research is to explore the level of intercultural knowledge that can enhance intercultural awareness among Malaysian secondary school students. Data was collected using a structured survey questionnaire to elicit responses from Form Four students in one national secondary school in Penang, Malaysia on their level of intercultural knowledge. The results of this study shows low level of intercultural knowledge among secondary school students and it indicates poor intercultural awareness among them in the contexts of intercultural knowledge. This suggest that classroom intervention is needed to improve the students’ intercultural knowledge and at the same time improve their intercultural sensitivity towards other cultures.